Mapping of Leading Sectors to Optimize Regional Economic Growth in West Sumatra Province - Sari, Yuria (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
West Sumatra's economic growth over the previous decade showed a downward trend from year to year. Therefore, it is necessary to accelerate economic growth by determining development priorities based on the leading sectors in each city district. This research uses Location Quotient (LQ), Differential Shift (DS), Dynamic LQ, and Klassen Typology analysis by processing West Sumatra GRDP data from 2019 to 2023. The results showed three advanced and fast-growing sectors: agriculture, fisheries and forestry, trade and education services. It is called a leading sector if it has a concentration of activity (comparative advantage), is highly competitive (competitive advantage), and is prospective for development. The agriculture, fisheries, and forestry sectors can be developed in Mentawai Islands, Tanah Datar, Padang Pariaman, and Pasaman. The trade sector is prioritized for development in South Solok and Padang City, as well as education services in Sijunjung, Padang Pariaman, Agam, Solok City, and Payakumbuh City. In addition to these three sectors, other sectors can be developed in their respective priority areas.